Rice Potassium Transporter OsHAK8 Mediates K+ Uptake and Translocation in Response to Low K+ Stress - Wang, Xiaohui; Li, Junfeng; Li, Fei; Pan, Yu; Cai, Dan; Mao, Dandan; Chen, Liangbi; Luan, Sheng (Frontiers in Plant Science, 2021)
Potassium (K+) levels in the soil often limit plant growth and development. As a result, crop production largely relies on heavy use of chemical fertilizers, presenting a challenging problem in sustainable agriculture. To breed crops with higher K-use efficiency (KUE), we must learn how K+ is acquired from the soil by the root system and transported to the rest of the plant through K+ transporters. In this study, we identified the function of rice K+ transporter OsHAK8 whose expression level is down-regulated in response to low K+ stress. When OsHAK8 was disrupted by CRISPR/Cas9-mediated mutagenesis, Oshak8 mutant plants showed a stunted growth especially underlow K+ conditions. Ion content analyses indicated that K+ uptake and root-to-shoot K+ transport was significantly impaired in Oshak8 mutants under low K+ conditions. As the OsHAK8 gene was broadly expressed in different cell types in the root and its protein was targeted to the plasma membrane, we propose that OsHAK8 serves as a major transporter for both uptake and root-to-shoot translocation in rice plants.